Use of Total Internal Reflection Raman (TIR) and Attenuated Total Reflection Infrared (ATR-IR) Spectroscopy to Analyze Component Separation in Thin Offset Ink Films after Setting on Coated Paper Surfaces. Issue 6 (June 2013) - Kivioja, Antti; Hartus, Timo; Vuorinen, Tapani; Gane, Patrick; Jääskeläinen, Anna-Stiina
The interactive behavior of ink constituents with porous substrates during and after the offset print process has an important effect on the quality of printed products. To help elucidate the distribution of ink components between the retained ink layer and the substrate, a variety of spectroscopic and microscopic analysis techniques have been developed. This paper describes for the first time the use of total internal reflection (TIR) Raman spectroscopy to analyze the penetration behavior of separated offset ink components (linseed oil, solid color pigment) in coated papers providing chemically intrinsic information rapidly, nondestructively, and with minimal sample preparation. In addition, the already widely applied technique of attenuated total reflection infrared spectroscopy (ATR-IR) was evaluated in parallel and compared. The results of the ATR-IR Raman clearly revealed an improvement in uppermost depth resolution compared with values previously published from other nondestructive techniques, and the method is shown to be capable of providing new knowledge of the setting of thin (0.25–2 μm) offset ink films, allowing the spreading and the penetration behavior on physically different paper coating surfaces to be studied.